2015
DOI: 10.1104/pp.114.252106
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-CpG-Binding Domain Protein MBD7 Is Required for Active DNA Demethylation in Arabidopsis  

Abstract: Although researchers have established that DNA methylation and active demethylation are dynamically regulated in plant cells, the molecular mechanism for the regulation of active DNA demethylation is not well understood. By using an Arabidopsis (Arabidopsis thaliana) line expressing the Promoter RESPONSIVE TO DEHYDRATION 29A:LUCIFERASE (ProRD29A:LUC) and Promoter cauliflower mosaic virus 35S:NEOMYCIN PHOSPHOTRANSFERASE II (Pro35S:NPTII) transgenes, we isolated an mbd7 (for methyl-CpG-binding domain protein7) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 38 publications
6
65
0
Order By: Relevance
“…Since IDAP1 and IDAP2 physically interact, and when either IDAP1 or IDAP2 mutates, IDM1 targeting, active DNA demethylation, and transcriptional gene silencing at specific loci were affected (Figs 4 and 5), we concluded that IDAP1 and IDAP2 cooperate to promote IDM1 targeting and H3K18 and H3K23 acetylation at many endogenous loci. MBD7 was previously found to assist in IDM1 targeting by binding to methylated DNA via its MBD motifs Li et al, 2015a;Wang et al, 2015). To summarize our findings on IDM1 targeting regulated by these three proteins, we proposed a model in which domesticated IDAP1 and IDAP2 coordinate with MBD7 to regulate IDM1 targeting (Fig 8).…”
Section: Discussionmentioning
confidence: 94%
“…Since IDAP1 and IDAP2 physically interact, and when either IDAP1 or IDAP2 mutates, IDM1 targeting, active DNA demethylation, and transcriptional gene silencing at specific loci were affected (Figs 4 and 5), we concluded that IDAP1 and IDAP2 cooperate to promote IDM1 targeting and H3K18 and H3K23 acetylation at many endogenous loci. MBD7 was previously found to assist in IDM1 targeting by binding to methylated DNA via its MBD motifs Li et al, 2015a;Wang et al, 2015). To summarize our findings on IDM1 targeting regulated by these three proteins, we proposed a model in which domesticated IDAP1 and IDAP2 coordinate with MBD7 to regulate IDM1 targeting (Fig 8).…”
Section: Discussionmentioning
confidence: 94%
“…ROS1 can remove the 5mC base and nick the DNA backbone, leaving a single nucleotide gap that is filled with an unmethylated cytosine through a base excision repair pathway 913 . An anti-silencing protein complex containing methyl-DNA binding protein 7 (MBD7), increased DNA methylation 1 (IDM1), IDM2, and IDM3, was recently discovered to regulate ROS1 targeting, and in turn DNA demethylation 1416 . In Arabidopsis, some TEs show lower expression levels in ros1 mutants due to increased DNA methylation 15,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The raw sequence data were demultiplexed and converted to fastq files using bcl2fastq2 Conversion Software (version v2.16.0) under default parameters. The DNA methylation was analyzed according to Zhao et al (2014) and Wang et al (2015).…”
Section: Bs-seqmentioning
confidence: 99%